Proton/hydroxide conductance and permeability through phospholipid bilayer membranes. - Gutknecht, J (1987)
Proton/hydroxide (H+/OH-) permeability of phospholipid bilayers is several orders of magnitude higher than alkali or halide ion permeabilities at pH 7. The objective of this study was to determine the mechanism(s) of H+/OH- conductance and permeability through planar phospholipid bilayer membranes. Membranes were formed from decane solutions of bacterial phosphatidylethanolamine, diphytanoyl phosphatidylcholine, or egg phosphatidylcholine plus cholesterol. At pH 7, H+/OH- conductance (GH/OH) ranged from 2 to 6 nS.cm-2, corresponding to H+/OH- "net" permeabilities of (0.4-1.6) X 10(-5) cm.sec-1. GH/OH was inhibited by serum albumin (fatty acid-free), phloretin, and low pH. GH/OH was increased by chlorodecane, long-chain fatty acids, and voltages greater than 80 mV. Water permeability and GH/OH were not correlated. The results suggest that the H+/OH- charge carrier (i) is primarily anionic, (ii) crosses the membrane via nonpolar pathway(s), and (iii) can be removed from the membrane by "washing" with serum albumin. The simplest explanation is that the phospholipids contain weakly acidic contaminants that act as proton carriers at neutral pH. However, at low pH or in the presence of inhibitors, a "background" GH/OH remains that may be due to other mechanisms.